Nationwide surveillance of azole-resistant Aspergillus fumigatus environmental isolates in Greece: detection of pan-azole resistance associated with the TR46/Y121F/T289A cyp51A mutation. (20th August 2020) - Siopi, Maria; Rivero-Menendez, Olga; Gkotsis, Georgios; Panara, Anthi; Thomaidis, Nikolaos S; Alastruey-Izquierdo, Ana; Pournaras, Spyros; Meletiadis, Joseph
Abstract: Background: Acquired azole resistance (AR) in Aspergillus fumigatus emphasizes the importance of the One Health multisectorial approach. The prevalence of azole-resistant A. fumigatus in the environment of Greece is unknown. Methods: Between October 2016 and September 2017, a total of 716 soil samples were collected from 23 provinces and screened for AR using azole-containing agar plates. Recovered isolates were macro-/microscopically identified and colonies were counted. Azole susceptibility testing of A. fumigatus species complex (SC) isolates was performed (EUCAST E.DEF9.3.1). Azole-resistant A. fumigatus isolates were subjected to confirmatory molecular identification and sequencing of the cyp51A gene. Results: No yeasts were recovered, while multiple moulds grew on 695 (97%) samples. Overall, zygomycetes (most non- Mucor genera) grew on 432 (60%) samples, while Aspergillus spp. grew on 500 (70%) [410 (57%) Aspergillus niger SC; 120 (17%) Aspergillus terreus SC; 101 (14%) A. fumigatus SC; 34 (5%) Aspergillus flavus SC]. The mean ± SD soil load of Aspergillus spp. was 2.23 ± 0.41 log10 cfu/g (no differences among species). No azole-resistant non- A. fumigatus spp. isolate was detected. Itraconazole, voriconazole, isavuconazole and posaconazole MIC50 /MIC90 (MIC range) of A. fumigatus SC strains were 0.25/0.5 (0.25 to >8), 0.5/1 (0.25 to >8), 1/1 (0.125 to >8) and 0.06/0.125 (0.06–1) mg/L, respectively. Overall, 1/500 (0.2%) of Aspergillus isolates, and 1/101 (1%) of A. fumigatus SC isolates, was pan-azole-resistant (itraconazole, voriconazole, isavuconazole and posaconazole MIC >8, >8, >8 and 1 mg/L, respectively). The resistant isolate was recovered from organically grown raisin grapes treated with homemade compost and it was an A. fumigatus sensu stricto isolate harbouring the TR46 /Y121F/T289A mutation. The soil's load was higher compared with azole-susceptible strains (3.74 versus 2.09 log10 cfu/g). Conclusions: This is the first known report of environmental pan-azole-resistant A. fumigatus in Greece. Since data on Greek clinical isolates are lacking, this finding must alarm the systematic local surveillance of AR in medical settings.